Nuptial feeding is reflected in tissue nitrogen isotope ratio in female katydids - Joachimski, Michael; et al. (Functional Ecology, 2006)
1. During copulation male katydids transfer a protein-rich nuptial gift to females, which is ingested by the female. We hypothesized that female katydids are built at least partly from proteins assimilated from nuptial gifts. 2. We measured the ratio of nitrogen isotopes (δ15N) in the diet and tissue of sexually reproducing Isophya kraussii and obligate parthenogenetically reproducing Poecilimon intermedius. We used the δ15N of muscles as an indicator of the most recent diet and the δ15N of the cuticula as an indicator of the larval diet. 3. In free-ranging I. kraussi, muscular and cuticular δ15N of adult males was low, suggesting a plant diet. Cuticular δ15N did not differ between sexes, indicating that immatures of both sexes fed on similar diets. Female muscles were significantly more enriched in nitrogen-15 than female cuticula and also than male muscles, suggesting that adult females incorporated animal proteins and immature females plant material. 4. Female I. kraussii that were kept with males in captivity had higher δ15N in muscular tissue than in cuticula. Muscular δ15N of these females was also higher than that of muscle and cuticula of females held isolated from males, suggesting that incorporated nitrogen originated from nuptial gifts. 5. In parthenogenetically reproducing P. intermedius muscular and cuticular δ15N was almost identical, suggesting no additional uptake of insect proteins in the absence of nuptial gifts. 6. We therefore conclude that female I. kraussii substantially assimilate spermatophylax compounds for both egg production and body homeostasis. © 2006 The Authors.
UnivIS-Import:2015-03-09:Pub.2006.nat.dgeo.IGM.LG.nuptia
Keywords: Homeostasis; Isophya; Nitrogen source; Spermatophore; Stable isotopes